On the Noether property of singular integral equations with Cauchy kernels on a rectifiable curve - Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The paper deals with the theory of a complete singular integral equation with a Cauchy kernel. The classes of curves and given functions are extended and generalizations of the classical Noether theorems are proved. As a consequence of these theorems, the Noether property is established for the operators associated with this equation, which act into incomplete normed spaces.